Preservice teachers' transformative learning through field experience with emergent bilinguals in a dual language school. Issue 6 (1st November 2020) - Cho, Hyesun; Johnson, Peter
ABSTRACT: This qualitative study investigates the transformative learning of preservice teachers vis-à-vis reflective practice in field experience with emergent bilingual (EB) students. Teacher candidates in an elementary education program in the Midwestern United States worked with EB students and their teachers in a Spanish-English dual language school as a part of a TESOL methods course requirement. Using qualitative research data, such as reflections, language autobiographies, and focus group interviews, the study explores whether and in what ways preservice teachers experienced transformative learning in an unfamiliar educational environment. The findings reveal how teacher candidates underwent transformative learning in a dual language setting that caused them to initially experience discomfort and anxiety while working with EB students and their teachers. The importance of context as well as relationships with others in transformative learning is reaffirmed in the study. The researchers alert teacher education programs to provide preservice teachers with field experience in an unfamiliar context where they can experience transformative learning.